2010
DOI: 10.1037/a0019234
|View full text |Cite
|
Sign up to set email alerts
|

Slope-driven goal location behavior in pigeons.

Abstract: A basic tenet of principles of associative learning applicable to models of spatial learning is that a cue should be assigned greater weight if it is a better predictor of the goal location. Pigeons were trained to locate a goal in an acute corner of an isosceles trapezoid arena, presented on a slanted floor with 3 (Experiment 1) or 2 (Experiment 2) orientations. The goal could be consistently determined by the geometric shape of the arena; however, its position with respect to the slope gradient varied, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
38
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 55 publications
4
38
1
Order By: Relevance
“…Similarly to the effect reported in Cheng's study (1986), in the study of Nardi et al (2010), subjects were unresponsive to the best predictor (geometry in this case) and instead were using the ambiguous slope information to reorient. In summary, slope seems to be driving search behavior when its predictive value is equal to ( Nardi & Bingman, 2009a, 2009b or even lower ( Nardi et al, 2010) than that of another available cue.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Similarly to the effect reported in Cheng's study (1986), in the study of Nardi et al (2010), subjects were unresponsive to the best predictor (geometry in this case) and instead were using the ambiguous slope information to reorient. In summary, slope seems to be driving search behavior when its predictive value is equal to ( Nardi & Bingman, 2009a, 2009b or even lower ( Nardi et al, 2010) than that of another available cue.…”
mentioning
confidence: 77%
“…On the contrary, when the two cues are set in conflict, they choose approximately equally the slope--correct and feature--correct location. In a series of studies using the same animal model, same inclination, similar apparatus, and analogous procedures (providing slope plus geometric cues; Nardi & Bingman, 2009a, 2009bNardi et al, 2010), slope was always shown to have overwhelming control over searching behavior. Such a dependence on one type of information for solving a task, even when that information is not the most effective, is a key premise for a module in Fodor's sense (1983).…”
Section: Conflict Testmentioning
confidence: 99%
See 1 more Smart Citation
“…To further investigate the salience of slope, we carried out a follow--up experiment (Nardi et al 2010). Using the same set--up as in Nardi and Bingman (2009), again, we trained pigeons to locate food hidden in a corner of a trapezoid arena presented on a 20° slope.…”
mentioning
confidence: 99%
“…However, subsequent test trials revealed, again, that pigeons were searching the goal by virtue of its position relative to the slope-even though this was not a reliable predictor and led to a systematic error (searching at a geometrically incorrect corner). In sum, slope was being relied upon when it had equal (Nardi and Bingman 2009) and even less predictive validity (Nardi et al 2010) compared to other available cues. Such a strong dependence on a spatial cue is striking, and a similar effect in reorientation found by Cheng in 1986 led to the claim of modularity (in that case, geometry was dominating searching behavior, so it was referred to as "geometric module").…”
mentioning
confidence: 99%